Risk Factors for Metastasis at Initial Diagnosis With Ewing Sarcoma - Ye, Conglin; Dai, Min; Zhang, Bin (Frontiers in Oncology, 2019)
Abstract Purpose: We aimed to determine potential risk factors predictive of metastasis at initial diagnosis in Ewing sarcoma patients. Patients and methods: We enrolled selected patients diagnosed with Ewing sarcoma between 2004 and 2015 in the Surveillance, Epidemiology, and End Results (SEER) Program database. Demographic and clinical features of patients were extracted and analyzed to evaluate the potential predictive factors of higher risk of distant metastasis at presentation. We utilized descriptive statistics, univariate methods, and a series of regression models to analyze the significance of risk factors. Moreover, we conducted survival analysis in different metastatic sites through Kaplan-Meier analysis. Results: We identified 1,066 cases of Ewing sarcoma and 332 (31.1%) of the patients had metastasis at diagnosis. In the univariate logistic regression analysis, patients had higher probability of metastasis at initial diagnosis if they had a tumor located in the axial or cranial bones (OR = 1.38; 95% CI, 1.05 to 1.81) as well as a tumor size over 5 cm (OR = 2.16; 95% CI, 1.44 to 3.25). These two factors were still significant when analyzed in a multivariate logistic regression model controlling for age, location, and tumor size, which had univariate p-values < 0.1. When we excluded all the patients with missing data, a tumor in axial or cranial bones and tumor size larger than 5 cm remained significant for metastatic disease at initial diagnosis in the multivariate model. Patients with lung metastasis alone had a better Ewing sarcoma-specific survival than patients with bone metastasis alone or patients with two or more metastatic sites (p < 0.01). Conclusion: Ewing sarcoma patients with a tumor in the axial or cranial bones and a tumor size over 5 cm had an increased likelihood to have metastatic disease at initial diagnosis.